Magnetic semiconductors for spin electronics - Alaria, Jonathan (Trinity College (Dublin, Ireland). School of Physics, 2010)
The development of the relatively new field of spin electronics is based on the possibility of manipulating the spin of the electron through a structure. If one aspect is to develop new device architecture to inject, transmit, and detect spin polarised current, the materials involved in the fabrication of these structures plays a major role. In fact, if most of the standard electronic devices have been successfully translated in spin-based electronic devices, the magnetic bipolar transistor has not been demonstrated. The major obstacle for the construction of such device is the lack of a ferromagnetic semiconductor that can be bipolar. Other materials such as half metals have been studied extensively as potential spin polariser. The experiments described in this thesis are aimed to synthesise and characterise compoimds that have a strong potential to be integrated in spin electronic structures. It includes materials with a high Curie temperature, metallic conduction and a relatively high spin polarisation and ferromagnetic semiconductor. The fundamental properties of these materials have been studied thoroughly as well as the magnetic properties of diluted magnetic oxide.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin